2018
DOI: 10.3389/fphys.2018.00217
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Exosomal miRNAs in Rats With Pulmonary Neutrophilic Inflammation Induced by Zinc Oxide Nanoparticles

Abstract: It has been previously shown that inhaled zinc oxide nanoparticles (ZnO-NPs) can modulate inflammation. MicroRNAs (miRNAs) enclosed in exosomes have been identified as an important signature for inflammatory responses. However, the role of exosomal miRNAs during pathogenic inflammation has not been investigated. Healthy rats were exposed to ZnO-NPs (41.7 nm; 2, 4, and 8 mg/kg) or saline (control) via oropharyngeal aspiration. ZnO-NPs induced significant increases in the serum levels of interleukin 8 (IL-8), in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 51 publications
(57 reference statements)
0
21
0
Order By: Relevance
“…Studies have shown that different metal or metal oxide nanoparticles may elicit varying cellular patterns of inflammation and one cannot a priori assume that macrophages are the only cell type at play 40 . In another recent study, ZnO nanoparticles were found to trigger neutrophilic inflammation in rats and numerous microRNAs were shown to be selectively up- or downregulated in serum exosomes from ZnO-exposed animals when compared with controls 41 . Using single-particle inductively coupled plasma-mass spectrometry and other techniques, Logozzi et al 42 reported that primary human macrophages are capable of endocytosis of gold nanoparticles (20 nm) with subsequent discharge of the nanoparticles via exosomes.…”
Section: Exosomes: Message In a Bottlementioning
confidence: 95%
“…Studies have shown that different metal or metal oxide nanoparticles may elicit varying cellular patterns of inflammation and one cannot a priori assume that macrophages are the only cell type at play 40 . In another recent study, ZnO nanoparticles were found to trigger neutrophilic inflammation in rats and numerous microRNAs were shown to be selectively up- or downregulated in serum exosomes from ZnO-exposed animals when compared with controls 41 . Using single-particle inductively coupled plasma-mass spectrometry and other techniques, Logozzi et al 42 reported that primary human macrophages are capable of endocytosis of gold nanoparticles (20 nm) with subsequent discharge of the nanoparticles via exosomes.…”
Section: Exosomes: Message In a Bottlementioning
confidence: 95%
“…A distinct set of extracellular miRNAs in induced sputum and BALF has also been identified as being associated with the respiratory tract [31,115,116]. In a rat study, serum EVs were identified with 16 different proinflammatory miRNAs in response to zinc oxide nanoparticles [117]. Additionally, miR-155 has a role in the development of infiltration of inflammatory cells into the lungs and in airway remodeling [118].…”
Section: Evs In Ba Pathogenesismentioning
confidence: 99%
“…Moreover, alveolar and interstitial macrophages have been identified as important regulators of pathological lung processes [25,26]. Qiao et al provided evidence that the pulmonary inflammation induced by exposure to ZnO-NPs is through modulation of miRNA expression [27]. Fukui et al reported that the inflammatory response and also the oxidative stress induced by ZnO-NPs were prevented by co-treatment with ascorbic acid in human lung carcinoma A549 cells [24].…”
Section: Discussionmentioning
confidence: 99%